College baseball players` perception of their team climate and mental health - Erdész, A.; Fry, M. D.; Fry, A. C. (Journal of Human Sport & Exercise, 2023)
The purpose of this study, grounded in the Achievement Goal Perspective Theory (AGPT) and a Caring framework, was to examine the extent that collegiate baseball players` perceptions of their team climate (i.e., caring, task-, and ego-involving climate) predict their mental well-being. Baseball players (N = 127) completed measures assessing perceptions of team climate (Perceived Motivational Climate in Sport Questionnaire, Caring Climate Scale) and mental well-being (World Health Organization-Five Well-Being Index). Spearman correlation analysis revealed a positive relationship between the caring and task-involving climate scales, and mental well-being, respectively. In a full entry model linear regression, caring climate emerged as a positive predictor of mental well-being, explaining 25% of the variance of athletes` mental well-being scores. The findings suggest that encouraging coaches to foster a caring and task-involving climate might assist in enhancing collegiate athletes` mental well-being. Athletes perceiving a high caring and task-involving environment are more likely to experience improved mental well-being.